VD_FINDINFO Jug / 2016 / 147 vom 16. September 2015 - VD Tribunal cantonal (2015)
LÉSION CORPORELLE SIMPLE, RIXE, INDUCTION DE LA JUSTICE EN ERREUR, LÉGITIME DÉFENSE | 123 ch. 1 CP, 133 CP, 15 CP, 304 ch. 1 al. 2 CP